Syntactic Complexity and Communicative Moves of Applied Linguistics Research Article Abstracts: A Function first Approach - Rajab Esfandiari; Mohammad Ahmadi; Aynur Ismayilli Karakoç (Journal of Modern Research in English Language Studies)
There is currently a growing tendency to a meaning-based approach to the analysis of syntactic complexity in academic writing. While previous studies have offered illuminating insights into linguistic realizations of rhetorical structures in relation to syntactic complexity, they have typically analyzed lexicogrammatical features in a decontextualized manner. Drawing on a corpus-based cross-sectional design, this study takes a function-first approach to investigating the rhetorical functions of syntactically complex structures in research article (RA) abstracts in applied linguistics. To that end, a corpus of 270 texts from leading applied linguistics journals was constructed. Based on the model proposed by Pho (2008), we manually annotated the texts for the moves, and measured their syntactic complexity using phrasal, clausal, and global metrics. SPSS (version 25) was run for the analysis of data. Results of one-way MANOVA (multivariate analysis of variance) and Chi-square tests revealed significant variations among rhetorical moves in terms of clausal and phrasal complexity measures. The findings also showed that academic writers varied the complexity of their written structures according to their rhetorical goals. The results establish form-meaning mappings between syntactically complex structures and rhetorical functions. The findings carry pedagogical implications for student writers to adjust their prose using functionally appropriate complex structures following expert writers through comparing their own writing with that of expert writers to notice the gaps.